Aspectos físicos e mentais de pacientes com doença falciforme: um estudo sobre qualidade de vida - RODRIGUES, Camila Freitas de Andrade (2019)
Sickle cell disease (SCD) is a genetic disorder characterized by a type of hemoglobin mutant called hemoglobin S (or HbS), which causes distortion on red blood cells, leading them to take the form of a sickle or “half-moon". The clinical events of this disease are: chronic anemia, painful crises, recurrent infections, stroke, jaundice, ocular complications, gallstones, among other ones. These complications interfere with the quality of life (QoL) of these patients at an early stage when symptoms begin. The State of Maranhão has high SCD prevalence and Public Policies need to be adopted and continuously revised for the management of these patients. The objective of this study is to evaluate the QoL in individuals with SCD. For this purpose, a generic QoL questionnaire - called SF-36 - was applied to patients attending HEMOMAR outpatient clinic (Hematology and Hemotherapy Center of Maranhão), a state reference for monitoring hemoglobinopathies. 113 sickle cell patients were interviewed and sociodemographic, disease characteristics and laboratory tests (hemogram, fetal hemoglobin, lactate dehydrogenase and reticulocytes) were collected. The SF- 36 questionnaire was then applied. From 113 patients, 62,8% were female, with an average of 26 years old, 52,7% declaring themselves to have brown skin color and 80,5% living in the country side of the State, with low-income and with low level of education. About 92% had the SS subtype, the most serious one. The percentage of neonatal diagnosis was only 27.4%. Regarding the SF-36 questionnaires, the quality of life was classified as poor in relation to the physical component and good in the mental component. The use of hydroxyurea - the only medication approved in Brazil for the control and prevention of pain crises - promoted an improvement in the physical domain of patients with SCD, however, without relation to the prevalence of clinical complications. HbF levels greater than or equal to 20% had positive effects on the mental component of patients with the disease. Having had their QoL impaired by the disease, sickle cell patients need State actions sensitive to this Public Health problem.